Pluronic F-68 Improves Callus Proliferation of Recalcitrant Rice Cultivar via Enhanced Carbon and Nitrogen Metabolism and Nutrients Uptake - Kok, Andrew De-Xian; Mohd Yusoff, Nur Fatihah; Sekeli, Rogayah; Wee, Chien-Yeong; Lamasudin, Dhilia Udie; Ong-Abdullah, Janna; Lai, Kok-Song (Frontiers in Plant Science, 2021)
Pluronic F-68 (PF-68) is a non-ionic surfactant used in plant tissue culture as a growth additive. Despite its usage as a plant growth enhancer, the mechanism underlying the growth promoting effects of PF-68 remains largely unknown. Hence, this study was undertaken to elucidate the growth promoting mechanism of PF-68 using recalcitrant MR 219 callus as a model. Supplementation of 0.04% PF-68 (optimum concentration) was shown to enhance callus proliferation. The treated callus recorded enhanced sugar content, protein content and glutamate synthase activity as exemplified in the comparative proteome analysis showing protein abundance involved in carbohydrate metabolism (alpha amylase), protein biosynthesis (ribosomal proteins) and nitrogen metabolism (glutamate synthase) which are crucial for plant growth and development. Moreover, an increase in nutrients uptake was also noted with potassium topping the list, suggesting a vital role of K in governing plant growth. In contrast, 0.10% PF-68 (high concentration) induced stress response in the callus, revealing an increment in phenylalanine ammonia lyase (PAL) activity, malondialdehyde content and peroxidase activity, which were consistent with high abundance of PAL, peroxidase and peroxiredoxin proteins detected and concomitant with reduced level of esterase activity. The data highlighted that incorporation of PF-68 at optimum concentration improved callus proliferation of recalcitrant MR 219 through enhanced carbohydrate metabolism, nitrogen metabolism and nutrient uptake. However, growth promoting effects of PF-68 is concentration dependent.